Onosma erzincanica (Boraginaceae: Lithospermeae), a new scree species from Turkey - Bi̇nzet Riza; Eren, Özkan (Phytotaxa, 2018)
A new species of Onosma (Boraginaceae: Lithospermeae) from the Erzincan province of eastern Anatolia, O. erzincanica, is described and illustrated. It belongs to the Haplotricha informal group which comprises the species with basal leaves covered by simple setae only. The species appears to be endemic to scree and is very narrowly distributed. The closest relative of O. erzincanica is O. obtusifolia Hausskn. & Sint. ex Riedl, which also occurs in Turkey. In addition to the its restriction to screes, it is primarily distinguished from O. obtusifolia by its golden yellow, shorter (14–17 mm) and clavate corollas, longer pedicels (2–5 mm), shorter filaments (ca. 4 mm), acute cauline leaves and having stems covered not only with 2–5 mm long patent setae but also with short hairs, and chartaceous to membranous leaves, calyx and bracts when dried. The geographical distribution of O. erzincanica and O. obtusifolia are mapped and an identification key for those species is provided. Pollen and nutlet micrographs of O. erzincanica are presented using scanning electron microscopy. The site conditions and conservation status of O. erzincanica are also considered.